UTILIZATION OF OPEN EDUCATION RESOURCES IN MORAL CREED SUBJECTS AT MA DARUL ULUM BOJONEGORO - Laila, Siti Alfin Nur; Hamid, Abdulloh; Hafiyusholeh, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Open Education Resources is a manifestation of the development of learning media in the modern era, open learning resources aim to improve the quality of education and facilitate the learning process. This type of research is fiel d research, namely research in which data is taken and carried out in the field by systematically analyzing and presenting facts about the state of the research object. This research was conducted using qualitative research methods. The aim of this research is to determine the competency, supporting and inhibiting factors of Aqidah Akhlak teachers at MA Darul Ulum Bojonegoro in utilizing Open Education Resources (OER) in the subject of Aqidah Akhlak. The results of the research found that the competence of Aqidah Akhlak teachers at MA Darul Ulum Bojonegoro was quite good, by utilizing learning resources searched via the internet they could integrate curriculum, modules and other learning tools. Supporting factors for using OER are easy access to open learning resources, freedom to innovate, opportunities for fellow teachers to collaborate in improving the quality of education, and teaching materials that can be adapted to the curriculum. The inhibiting factors in using OER are limited media tools, weak internet networks, teacher teaching habits, and limited time in using open learning resources